Reduction of power and lubricant oil consumption in milling process using a new SiO2 nanolubrication system - Sarhan, Ahmed Aly Diaa Mohammed; Sayuti, Mohd; Abd Shukor, Mohd Hamdi (Springer Verlag, 2012)
Manufacturing industries have been pressured to use less power and reduce pollution by the development of power-efficient and pollution-preventing policies from the government. However, quality and cost are of main concern in this agenda. In machining, the key solution for this issue is by increasing the effectiveness of existing lubrication systems as this reduces the power required to overcome the friction component in machining processes for less fuel consumption and pollution. In machining processes, in particular, improved lubrication systems will increase batch production rates with better product quality. Introducing nanolubrication reduces power consumption as the rolling action of a billion units of nanoparticles in the tool chip interface decreases the cutting forces significantly. Additionally, using nanolubrication in machining minimizes the consumption of the lubrication oil, which decreases pollution. Detailed analysis and implementation of nanolubrication in machining process with the proper parameter setup are mandatory to ensure the efficiency of implementing nanolubrication. In this research, SiO2 nanoparticles are mixed with ordinary mineral oil having 0.2 weight concentration. A proper sonification method is used to mix and suspend the particles thoroughly and efficiently. The results show a reduction in the coefficient of friction in the tool/chip interface. Hence, the cutting force and working power are reduced considerably compared with conventional lubrication systems. Consequently, considerable power savings, less oil consumption, and less pollution are achieved.